Factors Affecting Undergraduate Medical Science Students’ Motivation to Study during the COVID-19 Pandemic - Thomas Mayers; Bryan J. Mathis; C. Kiong Ho; Kazuya Morikawa; Naoki Maki; Koji Hisatake (Education Sciences, 2022)
In the current study, we investigated the motivational status and underlying factors of the motivational changes among Japanese medical science students brought by the COVID-19 pandemic. Two groups of second-year undergraduate medical science students (training to become medical technologists and/or medical science researchers) participated in this study in the summers of 2020 and 2021 by writing essays describing how the pandemic had affected their motivation to study. A content analysis of the motivation status and underlying factors (both motivating and demotivating factors) was conducted before statistical analysis was used to investigate possible differences between the sexes and the two groups. In total, 73 essays were included in the analysis. The students had increased motivation to study in both groups (89% and 62%, respectively); however, in Group 2021, 19% of the students (all women) had decreased motivation. Among the underlying reasons behind the increased motivation, students showed a desire to help/save others, contribute to the development of medical science, increase knowledge, and disseminate correct information. The demotivating factors were largely linked to online learning and the negative emotions associated with lockdown. Our findings suggest that, for Japanese medical science students, the COVID-19 pandemic has been an overall motivating experience for our students. However, the prolonged pandemic and lockdown measures could attenuate this and be particularly disruptive for women.